Panitumumab in combination with preoperative radiation therapy in patients with locally advanced RAS wild-type rectal cancer: results of the multicenter explorative single-arm phase 2 study NEORIT - Merx, Kirsten; Kripp, Melanie; Gaiser, Timo; Mai, Sabine; Kienle, Peter; Belle, Sebastian; Wenz, Frederik; Post, Stefan; Hofheinz, Ralf-Dieter (International journal of radiation oncology, biology, physics, 2017)
Purpose: Studies investigating combinations of anti-epidermal growth factor receptor monoclonal antibodies such as panitumumab or cetuximab with standard chemoradiation therapy protocols in rectal cancer have yielded disappointing results. Because of the supposed negative interaction of epidermal growth factor receptor inhibition and chemoradiation therapy, we conducted a phase 2 study using single-agent panitumumab in combination with radiation therapy in patients with RAS wild-type locally advanced rectal cancer. Methods and Materials: Patients with RAS wild-type locally advanced (clinical stage II or III) rectal cancer localized 0 to 12 cm from the anus were eligible for study participation. The primary objective of the study was to determine pathologic complete response (pCR). Secondary objectives comprised assessing the safety, surgical morbidity, clinical response, tumor downstaging, and tumor regression grading according to Dworak. Results: A total of 54 patients with a median age of 58 years were treated. In 3.7% of patients, pCR was achieved. Downstaging of the primary tumor or lymph nodes was seen in 65% of patients. No grade ≥2 hematologic toxicity was seen. The most common grade ≥3 nonhematologic toxicities were skin toxicity (24%) and diarrhea (10%). Conclusions: Panitumumab in combination with radiation therapy as neoadjuvant treatment for locally advanced rectal cancer showed a favorable toxicity profile but failed to meet the predefined pCR rate to justify further clinical trials.